IMPLEMENTATION OF ACTIVE LEARNING METHODS TO ENHANCE FOURTH-GRADE STUDENTS’ UNDERSTANDING OF ISLAMIC RELIGIOUS EDUCATION AT SDN INPRES JALA - Nurrahmi Nurrahmi; Ilham Ilham; Kaharuddin Kaharuddin (Jurnal Konseling Pendidikan Islam, 2026)
Islamic Religious Education (IRE) in elementary schools is required to foster an active learning process so that students can understand and implement religious concepts in their daily lives. However, teaching practices are still often dominated by teacher-centered methods. This study aims to analyze the implementation of active learning methods, their role in improving students' understanding, and the supporting and hindering factors. This study employed a qualitative approach with a case study design at SDN Inpres Jala. Data were collected through observations, interviews, and documentation involving IRE teachers, the principal, and fourth-grade students. The results showed that active learning methods were implemented systematically through planning, implementation, and evaluation stages using group discussions, question-and-answer sessions, presentations, and instructional media. The application of these methods proved to improve students' understanding, as evidenced by their ability to explain the material and relate it to daily life. The success of the implementation was supported by teacher competence, student motivation, and media availability, while differences in learning abilities and time constraints served as hindering factors. In conclusion, active learning can create a participatory, interactive, and meaningful IRE learning experience.